ANALISIS KESULITAN MAHASISWA PRAKTIKAN BAHASA JEPANG UNNES TAHUN 2015 DALAM MENGELOLA KELAS - Rohanawati, Retno; Diner, Lispridona; Wardhaningtyas, Setiyani (Universitas Negeri Semarang, 2017)
Practice teaching (PPL) is a student activity carried out in the school to integrate the theoretical knowledge gained from university. In accordance with nature as a means of forming ability of teacher that is applied directly in the field, the most important component in the PPL are teaching basic skills training. With basic skills and good teaching, a teacher will be to create a situation, condition and learning environment that can encourage students to get optimal achievement. Based on experience and interview as a preliminary study, the most important problems faced by students are to manage the class. The aim of this research is to find out what are the difficulties in managing a class, its causes and how to overcome these difficulties. The approach used in this research is quantitative descriptive. Population and sample in this research is a Japanese language education student who has done the teaching practice in 2015. A data collection technique in this research is using a questionnaire. A data analysis technique in this research is using descriptive percentages. Based on the survey results that the difficulty of Japanese language education student is controlling a rowdy class with percentages 82.3 %, providing for students who make noise with percentages 75.9 %, and developing the ability to ask with percentages 64.2%.  The cause of the difficulty is the lack of understanding of the character of students with percentages 82.3 %, lack of ability to master classes with many pupils capacity with percentages 78.4 %, in conveying the material is not really fluent with percentages 65.6%. The solutions most often performed by the students are observatory in the classroom when teaching colleagues with percentages 86.7 %.Practice teaching (PPL) is a student activity carried out in the school to integrate the theoretical knowledge gained from university. In accordance with nature as a means of forming ability of teacher that is applied directly in the field, the most important component in the PPL are teaching basic skills training. With basic skills and good teaching, a teacher will be to create a situation, condition and learning environment that can encourage students to get optimal achievement. Based on experience and interview as a preliminary study, the most important problems faced by students are to manage the class. The aim of this research is to find out what are the difficulties in managing a class, its causes and how to overcome these difficulties. The approach used in this research is quantitative descriptive. Population and sample in this research is a Japanese language education student who has done the teaching practice in 2015. A data collection technique in this research is using a questionnaire. A data analysis technique in this research is using descriptive percentages. Based on the survey results that the difficulty of Japanese language education student is controlling a rowdy class with percentages 82.3 %, providing for students who make noise with percentages 75.9 %, and developing the ability to ask with percentages 64.2%.  The cause of the difficulty is the lack of understanding of the character of students with percentages 82.3 %, lack of ability to master classes with many pupils capacity with percentages 78.4 %, in conveying the material is not really fluent with percentages 65.6%. The solutions most often performed by the students are observatory in the classroom when teaching colleagues with percentages 86.7 %.